Artificial Intelligence-Assisted Business Crime: Tantangan Regulasi Hukum Pidana di Indonesia - Aida Ardini; Pudjianto Gondosasmito (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Artificial Intelligence (AI) has transformed business crime into algorithm-driven misconduct that challenges conventional criminal law in Indonesia. This study examines regulatory gaps in imposing corporate criminal liability for AI-assisted business crime using normative legal research with statutory, conceptual, comparative and case approaches. The findings reveal three major deficiencies: the absence of AI-specific criminal norms, limitations of the traditional mens rea doctrine and weak corporate AI governance obligations. This study argues that AI adoption in criminal law requires a shift from individual fault to algorithmic governance failure, particularly in determining corporate criminal punishment and strengthening accountability in AI-driven business crimes.